Pengembangan Produk Kerajinan Tempat Tisu Ramah Lingkungan dari Limbah Kertas Bekas - Husnul Khotimah; Putri Sari Ayu; Dea Kamelia Putri; Juliana Juliana; Ahmad Shirotol (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
Waste paper is a type of waste that continues to increase in number from households, offices, and educational institutions. However, most of it has not been utilized optimally. The use of paper waste as a basic material for creative products can be an alternative solution to reduce environmental pollution. This research aims to develop tissue holder products from waste paper as creative products that are environmentally friendly, have aesthetic value, and have economic value. The method used is an experimental approach within the framework of Participatory Action Research (PAR) which actively involves the community in every stage of activities, ranging from planning, implementation, observation, to reflection. The results of the study show that tissue holders from waste paper have good visual appeal, adequate sturdiness, and can be further developed and become sustainable craft products